Examining the Malaysian state governments fiscal effort: The case of forest-based revenue 2000-2008 - Abdul Jalil, Ahmad Zafarullah; Harun, Mukaramah; Che Mat, Siti Hadijah (2012)
The paper seeks to examine the effort exerted by the state governments in Malaysia in collecting their forest-based revenue for the period of 2000-2008.The underlying objective is to see whether state governments are using its tax base optimally or not.These measures of tax efforts can later be used as a basis in calculating the amount of intergovernmental grants that the federal government can transfer to the state governments.The method used in order to measure the tax capacity and the tax effort is the representative revenue system (RRS) approach.The paper found that state governments in Malaysia differ significantly in both their tax capacity and tax effort. It is also found that the less developed states seem to be relatively more dependent on the forest-based revenues as compared to the more developed ones.